L’accès à l’eau courante des femmes migrantes à Ouagadougou : durabilité de l’accès et effet sur la survie des enfants - Stéphanie Dos Santos (VertigO)
In sub-Saharan Africa, 40 % of the population still does not have access to an improved source of water. In urban areas, despite of progress, this rate is the same as in 1990 because of the urban population growth largely due to migrations. However, diarrheal diseases are the second cause of child death in the world. In this context, we study the effect of water access on child survival focusing on the migrant status of the mother because they are responsible for child health for cultural and social reasons. Using longitudinal life-history data, we first examine factors affecting sustainable piped water access for migrant women in Ouagadougou, the capital-city of Burkina Faso. We then analyze factors affecting child survival focusing on water access and migrant status of the mother.